Effects of Microstructured and Anti-Inflammatory-Coated Cochlear Implant Electrodes on Fibrous Tissue Growth and Neuronal Survival - Lennart Fibranz; Wiebke Behrends; Katharina Wulf; Stefan Raggl; Lisa Kötter; Thomas Eickner; Soeren Schilp; Thomas Lenarz; Gerrit Paasche (Journal of Functional Biomaterials)
Cochlear implants are well established devices for treating severe hearing loss. However, due to the trauma caused by the insertion of the electrode and the subsequent formation of connective tissue, their clinical effectiveness varies. The aim of the current study was to achieve a long-term reduction in connective tissue growth and impedance by combining surface patterns on the electrode array with a poly-L-lactide coating containing 20% diclofenac. Three groups of six guinea pigs each (control, structure, structure with diclofenac in the coating) were implanted for four weeks. The hearing thresholds were measured before implantation and after 28 days, and impedances were monitored over time. After histological preparation, connective tissue growth and spiral ganglion neuron (SGN) survival were quantified. The hearing thresholds and impedances increased over time in all groups, showing no significant differences. The treatment groups showed increased damage in the cochlea, which appeared to be caused by the elevated parts of the microstructures. This seems to be amplified by the trauma model used in the current study. The impedances correlated with connective tissue growth near the electrode contacts. In addition, SGN survival was negatively correlated with the presence of connective tissue, both of which highlight the importance of successfully reducing connective tissue formation after cochlear implantation.